Uric Acid Nephrolithiasis: An Updated Review - Al-Qahtani, Haya Muhammad; Aldosari , Noura Saad; Almalki, Turki Mohammad Hasssan; Al Haili, Sarah Bhni Mohamed; Hakimi, Amal Jadah Abu Al-Qasim; Alharthi, Khalid Ayed Aoudh; Nabush, Marwah Mohammed; Hakami, Adel Ali; Aldawsari, Fahad nigiri; Aldalbahy, Naya Shujaa; Al matrad, Asmaa Mohammed Nasser; Al-Ghamdi , Mohammed Ali Abdul Hadi; et al. (Journal of Ecohumanism, 2024)
Background: Uric acid nephrolithiasis is a prevalent condition marked by the formation of kidney stones from uric acid crystal deposition. This disorder is often linked to hyperuricemia and acidic urine, with multiple risk factors, including obesity, diabetes, hypertension, and metabolic syndrome. Uric acid stones, which account for 5-40% of urinary stones globally, have historically caused significant pain and require advanced treatments. Aim: This review aims to update the understanding of uric acid nephrolithiasis, focusing on its etiology, epidemiology, pathophysiology, and current treatment strategies. Methods: The review synthesizes data from numerous studies on the biochemical formation, risk factors, and management of uric acid stones. It emphasizes the role of urinary pH, hyperuricosuria, low urine volume, and genetic predispositions in stone formation. The impact of diet, genetic disorders, and environmental factors is also discussed. Results: Uric acid stones primarily form under conditions of low urinary pH, which impairs the solubility of uric acid. Diets high in purines, dehydration, and metabolic disorders significantly increase the risk of stone formation. Key risk factors include hyperuricosuria, obesity, and acidic urine. Advances in treatment now allow the dissolution of many uric acid stones by increasing urinary pH and volume while managing hyperuricosuria. However, recurrence remains common, and the condition is associated with high healthcare costs. Conclusion: Uric acid nephrolithiasis remains a significant clinical challenge with diverse etiology and risk factors. Early diagnosis and intervention, including dietary modifications, adequate hydration, and medical management to increase urinary pH and reduce uric acid levels, are crucial in preventing recurrence. Continued research into the molecular mechanisms of stone formation and novel treatments is essential for improving patient outcomes.